Development of phantom for radiographic image optimization of standard patient in the lateral view of chest and skull examination - Miranda, Diana Rodrigues de Pina [UNESP]; Duarte, S. B.; Morceli, J.; Netto, T. Ghilardi (Elsevier B.V., 2006)
We present the construction of a homogeneous phantom to be used in simulating the scattering and absorption of X-rays by a standard patient chest and skull when irradiated laterally. This phantom consisted of Incite and aluminium plates with their thickness determined by a tomographic exploratory method applied to the anthropomorphic phantom. Using this phantom, an optimized radiographic technique was established for chest and skull of standard sized patient in lateral view. Images generated with this optimized technique demonstrated improved image quality and reduced radiation doses. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: homogeneous phantom; lateral view examination; optimized techniques; quality image